Dietary Inclusion of Black Soldier Fly (Hermetia Illucens) Larvae Meal and Paste Improved Gut Health but Had Minor Effects on Skin Mucus Proteome and Immune Response in Atlantic Salmon (Salmo Salar) - Weththasinghe, Pabodha; Lagos, Leidy; Cortés, Marcos; Hansen, Jon Øvrum; Øverland, Margareth (Frontiers in Immunology, 2021)
The present study investigated effects of dietary inclusion of black soldier fly larvae (BSFL) (Hermetia illucens) meal and paste on gut health, plasma biochemical parameters, immune response and skin mucus proteome in pre-smolt Atlantic salmon (Salmo salar). The seven-week experiment consisted of seven experimental diets: a control diet based on fishmeal and plant protein (Control-1); three BSFL meal diets, substituting 6.25% (6.25IM), 12.5% (12.5IM) and 25% (25IM) of protein; two BSFL paste diets, substituting 3.7% (3.7IP) and 6.7% (6.7IP) of protein and an extra control diet with 0.88% of formic acid (Control-2). The 6.25IM diet reduced enterocyte steatosis in pyloric caeca, improved distal intestine histology, and reduced IgM in distal intestine. The fish fed 12.5IM diet reduced enterocyte steatosis in pyloric caeca, improved distal intestine histology, had a higher plasma lysozyme content compared to 6.25IM, and tend to increase phagocytic activity in HK macrophages-like cells. On the other hand, 25IM diet improved distal intestine histology, but showed mild-moderate enterocyte steatosis in pyloric caeca, increased IFNγ and reduced IgM in distal intestine. In the case of BSFL paste diets, 3.7IP diet caused mild inflammatory changes in distal intestine, although it reduced enterocyte steatosis in pyloric caeca. The 6.7IP diet reduced enterocyte steatosis in pyloric caeca and improved distal intestine histology. Increasing level of BSFL meal in the diet linearly decreased plasma C-reactive protein, whereas increasing level of BSFL paste linearly increased plasma antioxidant capacity. Dietary inclusion of BSFL meal and paste had minor effects on the expression profile of proteins in skin mucus and no effects on immune markers in splenocytes. BSFL meal showed no negative effect on liver and muscle health as indicated by plasma alanine aminotranseferase, asparate aminotransferase and creatine kinase. The present study showed that replacing conventional protein sources with low to moderate levels of BSFL meal (6.25% and 12.5%) or paste (3.7% and 6.7%) reduced enterocyte steatosis in pyloric caeca, while replacing up to 25% with BSFL meal or 6.7% with paste improved distal intestine histology. Further, dietary inclusion of BSFL meal and paste had minor effects on skin mucus proteome and immune response in Atlantic salmon.